Sonorheometry assessment of platelet function in cardiopulmonary bypass patients: Correlation of blood clot stiffness with platelet integrin αIIbβ3 activity, aspirin usage, and transfusion risk. (February 2016) - Viola, Francesco; Lin-Schmidt, Xiefan; Bhamidipati, Castigliano; Haverstick, Doris M.; Walker, William F.; Ailawadi, Gorav; Lawrence, Michael B.
Abstract: Background: Impaired platelet function may underlie bleeding associated with cardiopulmonary bypass (CPB) and at present is incompletely evaluated with existing diagnostic technologies. Sonorheometry (SR) is a recently developed ultrasound-based technology that quantifies hemostasis and platelet activity from a blood sample by measuring ex vivo clot stiffness ( S ). We hypothesized that impaired platelet–fibrin interactions as assessed by SR would correlate with transfusion during CPB and history of prior aspirin therapy. Methods: Thirty-nine patients undergoing elective cardiopulmonary bypass (CPB) were enrolled following informed consent (University of Virginia IRB#14050) in a prospective observational pilot study to assess pre-operative platelet function and transfusion frequency. To assess platelet activity, abciximab was added to blood prior to SR and native S versus abciximab treated S created a differential test for platelet activity. Patient blood samples were activated with kaolin and SR was then used to measure clot stiffness. Patients were transfused with blood products as directed by clinical practice, with the surgical team blinded to SR results. Results: Blood clot stiffness with and without abciximab, was compared in a ratio test ( S/S abciximab ) named the Platelet Function Index (PFI). PFI was hypothesized to be positively correlated with platelet contributions through integrin αIIb β3 to clot stiffness. PFI for CPB subjects was lower for those receiving transfusions than those not receiving transfusions (p < 0.006). A receiver-operator characteristics (ROC) analysis correlating the PFI with the blinded surgical team's decision on transfusions that included platelet concentrates generated an area under the curve (AUC) of 0.79 (p < 0.001). Additionally, the mean value of PFI for subjects on aspirin therapy was lower than for those not on aspirin therapy (p < 0.02) and correlated with a 1.73-fold enhanced risk of receiving a peri-operative transfusion. Conclusion: Evaluation of platelet function with SR may help in the specification of blood transfusion needs in cardiac surgery and in the assessment of aspirin effects on risk of surgical bleeding. Graphical abstract: Highlights: Acoustic radiation force can be used to test blood clot stiffness in cardiac patients. Ex vivo clot stiffness tracked cardiopulmonary bypass patient overall hemostatic function closely. Platelet integrin αIIb β3 function could be correlated with overall risk of perioperative transfusions with an ROC of 0.79. CPB patients on aspirin therapy had lower clot stiffness and lower indices of platelet adhesive function.